A divergent method to key unit of tubulysin V through one-pot diastereoselective Mannich process of N, O-acetal with ketone. Issue 2 (11th January 2019) - Wang, Xue-Mei; Liu, Yi-Wen; Wang, Qiao-E; Zhou, Zhu; Si, Chang-Mei; Wei, Bang-Guo
Abstract: An efficient diastereoselective approach to access ( 4R )-hydroxy-( 2S )-substituted methyl ketones pyrroles skeleton4a-s has been developed through Mannich process involving N, O -acetal6 and ketones and propionaldehyde in excellent yield with high diastereoselectivity ( dr up to 99:1). In addition, the utility of this convenient Mannich process is demonstrated by the diastereoselective synthesis of Tuv fragment (2 ) and its analogue (18 ) of tubulysin V(1e) . Graphical abstract: